Improved infection control in the prevention of variant Creutzfeldt‐Jakob disease in Australia: costs and benefits - Trang Vu; Anthony Harris; Elena Gospodarevskaya (Elsevier, 2004)
Abstract Objective: To evaluate the costs and benefits of infection control strategies to prevent the transmission of variant Creutzfeldt‐Jakob disease (vCJD) in ophthalmic surgery in Australia. Methods: The reduction in the risk of iatrogenic transmission of vCJD from feasible infection control strategies was calculated using decision analytic models. A static model calculated the direct secondary transmission for surgical eye procedures, and a simple dynamic model estimated the change in the risk of a subsequent sustained epidemic over the longer term. The expected number of vCJD infections, their cost of care and years of life lost and the estimated cost of strategies included the direct costs of infection control measures were calculated taking a health system perspective. Results: The dynamic model (Markov process) predicted that from a hypothetical pool of as many as 100 primary vCJD cases there would be less than five iatrogenic infections in the next 30 years. If there are fewer than five primary cases the model predicted no secondary cases of vCJD. The costs of providing care for a vCJD case is estimated to be about 50,000, subject to considerable uncertainty. The minimum cost for using a partial infection control strategy to prevent an iatrogenic infection is likely to be in the order of several millions of dollars. Conclusions: Substantial public health investment would need to be made in order to reduce a low risk of iatrogenic transmission of vCJD. Given the likely number of cases of iatrogenic infection, and the order of magnitude of the costs of caring for cases of vCJD, it may be difficult to justify the high cost of risk reduction strategies.